Membangun empati siswa melalui bermain peran pada materi konflik sosial kelas VIII C SMP Lab UM - Soraya Mei Lina; Agus Purnomo (Universitas Negeri Malang, 2019)
This article supports expressing play activities in social conflict material to increase student empathy. Class action research (CAR) which consists of 4 stages namely; (1) Planning, (2) Implementing, (3) Observation, and (4) Reflection. PTK is conducted in two cycles in class VIII C with a total of 32 students. From the implementation process proves that with direct assistance through role playing, students can experience difficulties in direct interaction with the social. This happened because in some students the drama of totality. Can argue with role playing students can build empathy to respect other individuals.DOI: 10.17977/um022v4i12019p007